The Patient Patient: The Performance of Traditional versus Open‐Access Scheduling Policies. (17th December 2018) - Cho, David; Cattani, Kyle
ABSTRACT: We compare traditional and open‐access scheduling policies for outpatient medical practices in terms of the number of patients served and financial performance. Under a traditional scheduling policy, a patient schedules an appointment in advance and there is a significant possibility of patient no‐shows. In response, doctors overbook patients to reduce the idle time created by no‐shows. Under an open‐access scheduling policy, all appointments are scheduled the day of the appointment, thereby eliminating patient no‐shows but creating more randomness in the daily number of appointments. In contrast to earlier works, we consider the optimal average number of patients served and find that the open‐access policy may lead doctors to serve a greater number of patients but that the traditional policy may be more profitable by providing doctors more control over their schedule and ability to limit overtime.